Agricultural Land, Pesticides and Habitus of Muslim Farmers in Ngawi Regency (MUHARRIK: Jurnal Dakwah dan Sosial, 2021)
This article discusses the relationship between humans and nature in terms of the use of agricultural pesticides from the perspective of Pierre Bourdieu. Pesticides are an alternative route chosen by farmers in realizing in organic farming. The lifestyle of Indonesian farmers is the use of agricultural pesticides, which are considered effective in growing crops to get maximum results. The methodology in this article uses descriptive qualitative. The results obtained in this article indicate that farmers' lifestyle or habit of using pesticides is often carried out because pesticides are considered the right solution in farming. However, their use of course also refers to the doses and dosages that have been imposed based on state law provisions and religious recommendations. Islam. The use of pesticides must still pay attention to the conditions of the natural environment by understanding the control of Plant Destruction Organisms (OPT) concerning facilities and methods used in plant protection (including tools and machines, natural enemies, and pesticides) must not disturb health and threaten human safety, cause disturbance and damage to natural resources and or the environment. This government regulation is commensurate with the recommendation of the Islamic religion regarding the permissibility of using pesticides as a lifestyle for farmers, as long as it is not excessive. The use must be following the dosage, and not damage human health and the natural environment.